Repeat Consumption of Media Goods: Examining Factors Affecting Repeat Theatrical Viewing of Movies. Issue 4 (1st October 2016) - Chang, Byeng-Hee; Nam, Sang-Hyun; Chan-Olmsted, Sylvia M.; Kim, Hun
ABSTRACT: This study explored the factors affecting repeat theatrical viewing of movies. Integrating content, social influence, and access/competition variables, the analysis reveals that the drivers of theatrical repeat viewing are different from those for box office performance. For example, the effects of genre, transmedia content, and audience review were significant only for the latter and factors such as movie length, critics' review, and level of news coverage actually played a negative role in the repeat consumption.